Nationalism, ethnicity, citizenship : multidisciplinary perspectives - Barrett, Martyn D.,; Flood, Chris,; Eade, John, 1946- (Cambridge Scholars Publisher, 2011)
This title provides a detailed examination, from a variety of disciplinary perspectives, of contemporary issues relating to nationalism, ethnicity and citizenship.